Dampak Penyebaran Berita Hoaxs melalui Platform Tiktok : Persepsi Gen – Z di Tanjungpinang - Ferdian Nando Simanullang (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
This study examines the phenomenon of hoax news dissemination through the social media platform TikTok and its impact on Generation Z in Tanjung Pinang. The background of this research is based on the increasing intensity of TikTok usage among young people, making the platform not only a source of entertainment but also an alternative channel of information. The research employed a descriptive qualitative method, using in-depth interviews with ten respondents selected through purposive sampling. The findings reveal that although most members of Generation Z are aware of hoaxes, their ability to verify information remains limited, making them easily influenced by provocative viral content. The most common hoaxes encountered are related to political, health, and social issues, which may lead to public unrest and shape public perception. This study highlights the importance of digital literacy as the main defense against the flood of information in the new media era, as well as the need for collaboration among government, educational institutions, and society to strengthen critical awareness in the use of social media.